2019
DOI: 10.1186/s40510-019-0300-2
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar bone remodeling during maxillary incisor intrusion and retraction

Abstract: Background: Maxillary incisor protrusion is a prevalent dental deformity and is often treated by upper incisor intrusion and retraction. The mechanical loading triggers the resorption and apposition of the bone. Alveolar bone remodeling is expected to follow orthodontic tooth movement in a one-to-one relationship. However, in many cases, the outcomes are different. Alveolar bone might still remain thick causing lip protrusion and other aesthetic problems after treatment. Additional corrective procedures such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 18 publications
1
16
0
Order By: Relevance
“…Not much is known about the effects of the vertical change of the incisor after orthodontic movement on the periodontium; however, this aspect may be important in evaluating vertical bone loss. 41 A previous study reported a 5-mm extrusion in the projected incisors that developed dehiscence. 8 In the current study, the MIH measurement was designed to evaluate whether the incisors' extrusion or intrusion would cause any changes in thickness and height to the bone ridge and the interdental septum, as well as in F-CEJ-MBC and L-CEJ-MBC.…”
Section: Discussionmentioning
confidence: 95%
“…Not much is known about the effects of the vertical change of the incisor after orthodontic movement on the periodontium; however, this aspect may be important in evaluating vertical bone loss. 41 A previous study reported a 5-mm extrusion in the projected incisors that developed dehiscence. 8 In the current study, the MIH measurement was designed to evaluate whether the incisors' extrusion or intrusion would cause any changes in thickness and height to the bone ridge and the interdental septum, as well as in F-CEJ-MBC and L-CEJ-MBC.…”
Section: Discussionmentioning
confidence: 95%
“…These changes can be explained by the alveolar bone remodeling, which usually follows the orthodontic tooth movement. These changes were reported in numerous studies that indicated possible bone remodeling in adult patients after orthodontic treatment [ 16 19 ].…”
Section: Discussionmentioning
confidence: 58%
“…The purpose of the present study was to evaluate the change in palatal alveolar bone thickness and the factors affecting the resorption of the palatal alveolar bone caused by tooth movement of the maxillary central incisors. A previous study indicated that while upper incisors were intruded and retracted simultaneously, various labial side response was described 23 . In the present study, the difference between labial and palatal response was evaluated.…”
Section: Discussionmentioning
confidence: 99%